Removal of an Impaled Knife under Thoracoscopic Guidance - Seth Isenburg; Nicole Jackson; Riyad Karmy-Jones (Canadian Respiratory Journal)
Thoracoscopy is being increasingly utilized in stable patients to manage both blunt and penetrating injuries. The case of a patient who presented with a knife impaled in the chest is reported. The knife was able to be removed under thoracoscopic guidance, avoiding thoracotomy.